Hidden champions: Exploring supportive family relationships of youth experiencing homelessness. Issue 1 (18th July 2022) - Gallardo, Kathryn R.; Narendorf, Sarah C.; Markham, Christine M.; Swartz, Michael D.; Santa Maria, Diane
Abstract: The relationships that youth experiencing homelessness (YEH) have with supportive family members (i.e. those who provide them with social support) may be protective against risk behaviours and buffer adverse health outcomes. However, little is known about the nature of YEH's supportive family relationships and the type of social support that these family relationships offer them. Thus, we conducted in‐depth interviews with 30 YEH to examine the type of social support received from family relationships and to explore the social dynamics of these relationships. We found that many YEH not only continued to maintain relationships with family members after becoming homeless but also received emotional and/or instrumental support from these family members. Beyond providing this type of social support, family members served as a source of motivation for these youth. Additionally, YEH contributed to their family relationships and gained a sense of connectedness in return. Lastly, we found that YEH's family support was influenced by their family circumstances and their need for autonomy. Collectively, our findings suggest there may be a need for interventions designed to strengthen relationships with supportive family members among YEH, who may derive multiple positive benefits from relating with the 'hidden champions' in their lives.